Examining the relation between oral contraceptive use and attentional engagement in everyday life - Smith, Alyssa C.; Marty-Dugas, Jeremy; Smilek, Daniel (Frontiers in Human Neuroscience, 2023)
Oral contraceptives (OCs) used by women worldwide include artificial estradiol and progesterone, which can attach to receptors in the brain and potentially influence cognition. In the present studies, we examined the relation between OC use and self-reported everyday attention. We collected trait-level measures of mind wandering, attention-related errors, and attention lapses in undergraduate women using OCs (Study 1: OC group N = 471, Study 2: OC group N = 246) and naturally cycling women not using any form of hormonal contraceptives (Study 1: Non-OC group N = 1330, Study 2: Non-OC group N = 929). In Study 1, we found that women using OCs reported significantly less spontaneous and deliberate mind wandering than naturally cycling women and no differences between groups on attention-related errors and attention lapses. In Study 2, our findings indicated no significant differences between groups on any of our attention measures. Regression analyses controlling for depression symptoms and semester of data collection found that OC use did predict unique additional variance on some attention measures, but these effects were small and unreliable across the two studies. Taken together, our data suggests there is little evidence that OC use is related to differences in attentional engagement in everyday life.